Hubungan Lama Kesakitan Ispa Dan Diare Dengan Status GiziAnak Balita Di Wilayah Kerja Puskesmas PolokartoSukoharjo - Nusantoro, Budhi Utomo; , Luluk Ria Rakhma, S.Gz., M.Gizi; , Endang Nur Widiyaningsih, SST, M.Si. Med (2016)
Background : In the golden age of children under five, the attention to their nutritional status must be a priority because malnutrition will affect the quality of child development. Infection is one of the direct factors affecting the nutritional status of children. Objective : To understand the relationship between the suffering duration of acute respiratory infections (ARI) and diarrhea and the nutritional status of children under five years old in the working area of Polokarto health care center, Sukoharjo Methodology : This research is an observational analysis with cross sectional approach. The research subjects are 98 children whose ages are ranged from 1- 5 years old. The data was collected by using proportional random sampling. ARI and diarrhea data were obtained by using the provided questionnaires and nutritional status were obtained from anthropometric measurements. Data were analyzed by using Spearman rank correlation test. Result : There are 59,2% children under five years old do not have ARI, 40.8% have ARI. The average suffering duration of ARI is 2,5 days. 83,7% of children under five years old do not have diarrhea and 16,3% have diarrhea with 0,47 days for the average suffering duration. The majority of children under five have good nutritional status (74,5%) with the average value of z-score is -1.2. Spearman rank test result for the relationship between the suffering duration of ARI and nutritional status shows the p value = 0.315 Spearman rank test result for the relationship between the suffering duration of diarrhea and nutritional status showed the p value = 0.559. Conclusion : There is no correlation between the suffering duration of ARI and diarrhea and the nutritional status of children under five years old in the working area of Polokarto health care center,